A study of student’s English speaking skill through schoology - Erik Nurdiansah; Fauzi Miftakh; Nina Puspitaloka (Politeknik Negeri Bali, 2021)
This study is aimed to find out the strengths and the weaknesses of schoology in teaching and learning speaking and the student’s perception on the implementing schoology in teaching and learning speaking. For this research the researchers took six students of 10th grade. Qualitative was chosen as research approach to answer the research questions, while the research methodology used in this paper was narrative inquiry. The research instruments that was used in this research are interview guideline, students’ and teachers’ reflective journal questions. The data were collected by doing the three techniques: interview, reflective journal and documentation. The data analysis used thematic analysis. The finding of this research is divided into two themes: understanding schoology as an instructional media in learning speaking and student's experience of schoology in learning speaking. In this research, the researchers find out some the strengths and the weaknesses of the schoology and the students' perception of the implementing schoology in teaching and learning speaking. (1) The advantages of using schoology in teaching and learning speaking are easy to access, easy to send assignment, students can get direct feedback from the teacher personally, the features are appealing. There is no significant weaknesses of the schoology in speaking, the only weaknesses that teachers and students face are those related to internet signals. (2) The students' perception towards the implementation of schoology has a positive perception and impression because they can express their ideas in the process of learning speaking. As the conclusion, schoology is very helpful in teaching and learning speaking process, however, the teachers need to pay more attention on the weaknesses. From these research, we can anticipate the troubles that will happen and hopes that this research becomes alternative for teachers in teaching speaking.